VISUAL BRANDING BROWNIES NONA VITA DI RIMBO BUJANG - Iqbal Lupi Maulana, Dra. Jupriani, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Brownies is one product that is highly developed and favored by all circles. But in Rimbo Bujang, Brownies are still considered expensive food or rich people's food, besides people are very interested in foods that have a modern feel. Brownies can also be used as a home-based business field. Mrs. Vita is a person who saw the opportunity. For this reason, Mrs. Vita enthusiasticed to asked for help from the writer in comparing her products. The main purpose of the brand design is to build, increase or increase brand equity, the main dimensions of which are brand awareness (brand awareness) and brand loyalty by consumers. Stages of design starts from data collection, data analysis and design.The process of collecting data through observation, interviews and documentation, while the process of data analysis using the SWO T method. The design produces a Manual Book design as the main media, and some supporting media, namely:business cards, sales invoices, letterhead, envelopes, stamps, posters, x banners, t-shirts, Apron, Chef hats, napkins, packaging, stickers, and social media pages.Key Words : Visual Branding, Brownies, Rimbo, Brand.